Create Success Agile social learning - Doyle, Jon (New York The McGraw-Hill, 2013)
Research shows the best chance a student has at success and persistence in college is to get involved and engaged with the school within 30 days of orientation through relationships, whether with an instructor, staff, or other students. This title provides students and instructors with the tools needed to foster these relationships.
Keywords: College student orientation -- United States. College students -- United States -- Life skills guides. Study skills -- United States. Vocational guidance -- United States. Education, Higher -- Curricula -- United States. College student orientation. College students. Education, Higher -- Curricula. Study skills. Vocational guidance. United States